Peran Marketing Mix (7P) dalam Mempengaruhi Pemanfaatan Pelayanan Rawat Inap: Studi Persepsi Pasien di Rumah Sakit Umum Daerah X - Kahendra, Fariz; Lestari, Paramita Boni; Efkelin, Ria; Gunawan, Tania; Aurellia, Kharina Aisyah (KOLONI, 2026)
Hospital marketing mix is a set of controllable variables used to influence patients’ decisions in choosing healthcare services. This study was motivated by the low Bed Occupancy Rate (BOR) at RSUD X, which has not yet reached the ideal standard, with an average of 43.96%. This study aims to analyze the effect of patients’ perceptions of the marketing mix (7P) on the utilization of inpatient services at RSUD X. This research employed a quantitative method with a cross-sectional approach. The sample consisted of 122 inpatients selected using probability sampling with a simple random sampling technique. Data analysis was conducted to examine the relationship between patients’ perceptions of the marketing mix and inpatient service utilization. The results showed that most respondents had a positive perception of the marketing mix with good service utilization (53 respondents; 40.2%), while respondents with poor perception and low utilization accounted for 61 respondents (50.0%). Statistical analysis indicated a significance value of 0.000 (<0.05) with a correlation coefficient of 0.752, categorized as strong. This indicates a significant effect of patients’ perceptions of the marketing mix on inpatient service utilization at RSUD X. It is recommended that the hospital improve responsiveness to patient complaints, enhance the service environment, and conduct regular satisfaction surveys to increase service utilization.